Investigating the Acceptance of Voice User Interfaces for Users With Disabilities - Dae Hwan Jin; Yong Min Kim; Yushin Lee (IEEE Access)
It is known that the voice user interface (VUI) is very useful for people with disabilities. However, previous studies related to VUIs for people with disabilities have usually focused on developments and evaluations of new systems, with acceptance of commercially available VUI systems receiving little attention. The purpose of this study is to investigate acceptance of commercially available VUI systems for users with disabilities and the major factors influencing acceptance by people with different disabilities and their reasons for using, or not using, VUI systems. A survey was conducted of people with disabilities who had already used one or more VUI systems. The collected data were analyzed statistically and qualitatively. The results showed the acceptance of VUI systems and the relationships among the acceptance factors given, revealing some differences between users with different types of disabilities. The results of this study also provided insights into the usability and user experience of VUI systems. Although there are some limitations, this study could contribute to the related research fields by investigating acceptance of VUI systems for users with disabilities from their own perspectives.